Modelling and simulation of the mechanical behaviour of weft-knitted fabrics for technical applications: Part I: General considerations and experimental analyses - Araújo, M. (2003)
This paper is in four parts. The first is related to general considerations and experimental analyses, and each of the others is related to different approaches to theoretical analyses of the mechanical behaviour of weft-knitted fabrics and weft-knitted reinforced composites made of glass fibre. The objective is to find ways of improving the mechanical properties and simulating the mechanical behaviour of knitted fabrics and knitted reinforced composites, so that the engineering design of such materials and structures may be improved. In Part III the second model is presented, and this is a 2D model based on FEA (finite element analyses). A plain weft-knitted fabric, based on the simple loop structure, is simplified and represented by a 2D hexagonal structure constructed by non-linear truss elements. The characteristics of the truss elements for FEA simulation are obtained from experimental results through an analytical method when a loop is converted to a FEA model. The elongation deformation is simulated in one, two and multiple directions. The model can also be used to calculate a planar knitted fabric for deformation to fit a 3D spherical mould.